Pathway for the Biosynthesis of the Pigment Chrysogine by Penicillium chrysogenum - Viggiano, Annarita (Appl Environ Microbiol, 2018)
Chrysogine is a yellow pigment produced by Penicillium chrysogenum and other filamentous fungi. Although the pigment was first isolated in 1973, its biosynthetic pathway has so far not been resolved. Here, we show that deletion of the highly expressed nonribosomal peptide synthetase (NRPS) gene Pc21g12630 (chyA) resulted in a decrease in the production of chrysogine and 13 related compounds in the culture broth of P. chrysogenum. Each of the genes of the chyA-containing gene cluster was individually deleted, and corresponding mutants were examined by metabolic profiling in order to elucidate their function. The data suggest that the NRPS ChyA mediates the condensation of anthranilic acid and alanine into the intermediate 2-(2-aminopropanamido)benzoic acid, which was verified by feeding experiments of a ΔchyA strain with the chemically synthesized product. The remainder of the pathway is highly branched, yielding at least 13 chrysogine-related compounds. IMPORTANCE Penicillium chrysogenum is used in industry for the production of β-lactams, but also produces several other secondary metabolites. The yellow pigment chrysogine is one of the most abundant metabolites in the culture broth, next to β-lactams. Here, we have characterized the biosynthetic gene cluster involved in chrysogine production and elucidated a complex and highly branched biosynthetic pathway, assigning each of the chrysogine cluster genes to biosynthetic steps and metabolic intermediates. The work further unlocks the metabolic potential of filamentous fungi and the complexity of secondary metabolite pathways.